2008
DOI: 10.1080/13645700801969816
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced stem cell activation and its implication for cardiovascular and skeletal muscle regeneration

Abstract: A number of publications have provided evidence that exercise and physical activity are linked to the activation, mobilization, and differentiation of various types of stem cells. Exercise may improve organ regeneration and function. This review summarizes mechanisms by which exercise contributes to stem cell-induced regeneration in the cardiovascular and the skeletal muscle system. In addition, it discusses whether exercise may improve and support stem cell transplantation in situations of cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…Studies have shown that exercise enhances the effect of injected stem cells by inducing mobility of the cells, activating and proliferating the local stem cells, promoting muscle angiogenesis and release of cytokines and nerve growth factors. Hence, neurorehabilitation compliments with the stem cell therapy [100].…”
Section: Importance Of Neurorehabilitationmentioning
confidence: 99%
“…Studies have shown that exercise enhances the effect of injected stem cells by inducing mobility of the cells, activating and proliferating the local stem cells, promoting muscle angiogenesis and release of cytokines and nerve growth factors. Hence, neurorehabilitation compliments with the stem cell therapy [100].…”
Section: Importance Of Neurorehabilitationmentioning
confidence: 99%
“…SP cells exist in a variety of organs, such as bone marrow, skeletal muscle, liver, brain, lung, skin and heart [ 72 ] , and it has been demonstrated that these SP cells increase in number within 3 days after cardiac injury, co-expressing cardiomyocyte-specifi c sarcomeric proteins [ 60 ] . Cardiac stem cells have been described as dividing symmetrically and asymmetrically [ 102 ] . When stem cells divide symmetrically, 2 self-renewing daughter cells are formed and expansion of stem cell compartment occurs.…”
mentioning
confidence: 99%
“…On the other hand asymmetrical division ensues that one daughter stem and one daughter amplifying cell are obtained, resulting in cell diff erentiation [ 55 ] . In fact, the preservation of a pool of primitive cardiac stem cells and of a myocyte progeny, together with endothelial and smooth muscle is accomplished by a replication mechanism in which CSCs gives rise to one daughter and one daughter-committed cardiac stem cell [ 102 ] . These resident CSCs are stored in niches that are scattered throughout the myocardium, and it has been suggested that distinct levels of wall stress may infl uence their distribution.…”
mentioning
confidence: 99%
See 2 more Smart Citations